2013
DOI: 10.1007/s11626-013-9693-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dots induce heat shock-related cytotoxicity at intracellular environment

Abstract: Quantum dots (QDs) are semiconductor nanocrystals with unique optical properties. Different proteins or polymers are commonly bound to their surfaces to improve biocompatibility. However, such surface modifications may not provide sufficient protection from cytotoxicity due to photodegradation and oxidative degradation. In this study, the cytotoxic effects of QDs, CdTe, and CdSe/ZnS were investigated using cadmiumresistant cells. CdTe QDs significantly reduced cell viability, whereas, CdSe/ZnS treatment did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…Excessive production of ROS was one of the common mechanisms for the toxic effects of nanomaterials; the ROS can react with macromolecules such as proteins, DNA, lipids etc., which affects the structure and function of macromolecules, and then causes cell oxidative damage (Cho et al, ; Juzenas, Generalov, Juzeniene, & Moan, ; Kermanizadeh, Gaiser, Johnston, Brown, & Stone, ; L. Liu et al, ; Migita et al, ; Skalickova et al, ; Tsay & Michalet, ; Wang & Tang, ; Wang, Gao, & Su, ; Yong & Swihart, ). The Tang et al study outcomes showed that CdTe QDs and cadmium chloride caused ROS to increase significantly in zebrafish liver cells, which lead to DNA strand breaks, meanwhile, antioxidant genes and DNA repair gene expression was significantly upregulated (Tang, Allagadda, et al, ).…”
Section: Toxic Effects Of Quantum Dotsmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive production of ROS was one of the common mechanisms for the toxic effects of nanomaterials; the ROS can react with macromolecules such as proteins, DNA, lipids etc., which affects the structure and function of macromolecules, and then causes cell oxidative damage (Cho et al, ; Juzenas, Generalov, Juzeniene, & Moan, ; Kermanizadeh, Gaiser, Johnston, Brown, & Stone, ; L. Liu et al, ; Migita et al, ; Skalickova et al, ; Tsay & Michalet, ; Wang & Tang, ; Wang, Gao, & Su, ; Yong & Swihart, ). The Tang et al study outcomes showed that CdTe QDs and cadmium chloride caused ROS to increase significantly in zebrafish liver cells, which lead to DNA strand breaks, meanwhile, antioxidant genes and DNA repair gene expression was significantly upregulated (Tang, Allagadda, et al, ).…”
Section: Toxic Effects Of Quantum Dotsmentioning
confidence: 99%
“…Excessive production of ROS was one of the common mechanisms for the toxic effects of nanomaterials; the ROS can react with macromolecules such as proteins, DNA, lipids etc., which affects the structure and function of macromolecules, and then causes cell oxidative damage (Cho et al, 2007;Juzenas, Generalov, Juzeniene, & Moan, 2008;Kermanizadeh, Gaiser, Johnston, Brown, & Stone, 2014;L. Liu et al, 2015;Migita et al, 2014;Skalickova et al, 2013;Tsay & Michalet, 2005;Wang & Tang, 2018;Wang, Gao, & Su, 2010;Yong & Swihart, 2012 Bcl-2 were obviously downregulated, ATG3, ATG7, ATG13 and ATG14 were upregulated, AIFM2, APAF1 and BAD were upregulated. Paesano et al, 2016 Realgar QDs: 5.48 nm HepG2 cells 0-80 μg ml −1 Cell death and MMP decreased in a dose-dependent manner, IC 50 for HepG2 after 6 h was 23 μg ml −1 ;Bcl-2 showed dose-dependent decrease and Bax was increased at the level of gene and protein;ER stress gene GRP78 and CHOP increased by 30-and 10-fold, respectively.…”
Section: Reactive Oxygen Species and Oxidative Stressmentioning
confidence: 99%
“…1 Several transcriptomic analyses indicate that exposure to any stress agents, especially to toxic compounds, prompts changes in gene expression profile, especially genes related to stress response 2-4 , reactive oxygen species (ROS) metabolic processes 2 , 3 , DNA damage response 2 , and cell redox homeostasis 2 . In order to maintain cellular integrity and survival, nanomaterial exposure (i.e., silver nanoparticles (NPs) 5 , silica NPs 6 , quantum dots (QDs) 7 , or carbon nanotubes 8 ) triggers the production of a set of heat shock proteins (HSPs). 9 The HSPs are a sub-group of molecular chaperons; accessory proteins that manage mechanisms crucial for the cell survival and maintenance including protein folding and assembly mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In order to maintain cellular integrity and survival, nanomaterial exposure ( i.e. , silver nanoparticles (NPs), silica NPs, quantum dots (QDs), or carbon nanotubes) triggers the production of a set of HSPs . The HSPs are a subgroup of molecular chaperones: accessory proteins that manage mechanisms crucial for the cell survival and maintenance including protein folding and assembly mechanisms .…”
mentioning
confidence: 99%